PELATIHAN PENANGANAN DAN PENCEGAHAN CEDERA DALAM OLAHRAGA BAGI SISWA SMP NEGERI 18 BANDA ACEH - zulheri Is; syahrianursaifi; Munzir (CV Abid Abadi Jaya, 2025)
This community service activity aimed to improve students’ knowledge and skills in handling and preventing sports injuries through a systematic and applicable training program. The activity was conducted at SMP Negeri 18 Banda Aceh involving 30 students as participants. The method used was an educative-participatory approach through interactive lectures, demonstrations, and direct practice using the RICE method (Rest, Ice, Compression, Elevation). Data were collected through pre-test and post-test to measure students’ knowledge improvement. The results showed a significant increase in the average score from 55.3 in the pre-test to 80.7 in the post-test, representing a 46% improvement. In addition, 90% of students were able to correctly perform injury handling techniques, and the level of active participation reached 95%. These findings indicate that the training was effective in enhancing students’ understanding and practical skills. The activity also had a positive impact on students’ awareness of the importance of injury prevention in sports activities. Therefore, training on sports injury management and prevention can be an effective, safe, and sustainable strategy in physical education learning in schools.